Effects of no-take marine reserves on fish assemblages in Brazil: an assessment using stereo-videos - Rolim, Fernanda Andreoli [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The establishment of no-take marine reserves (NTRs), i.e. areas with total fishing restrictions, has been an alternative worldwide aiming to preserve both biodiversity and ecosystem functions. Brazil has important NTRs with few studies describing their relevance and efficiency for marine life. With this, the central objective of this thesis was to evaluate the effects of NTRs on fish assemblage, testing the hypothesis that the differences in richness, abundance, biomass and fish body size is more explained by protection status than environmental characteristics. Thus, innovative techniques in Brazil, Baited Remote Underwater stereo-Videos (stereo-BRUVs) and Diver Operated stereo-Videos (stereo-DOVs) were tested in the Southwestern Atlantic, comparing with traditional visual census (stationary point count and belt transects), and used to analyze the effects of the Tupinambás Ecological Station and Abrolhos Marine National Park on fish assemblages. For this, fish assemblage characteristics, such as richness, abundance, biomass and body size, were compared to areas where fishing is allowed, and the habitat complexity was estimated through the footages. Concerning methods comparison, stereo-DOV showed to be more effective, sampling more richness and abundance within less effort, and Stereo-BRUVs showed to sample a very specific assemblage, comprised mostly by mobile and large bodied fish species, usually targeted by fisheries. Within both NTRs evaluated, target species characteristics was explained by protection status, while non-target species assemblage were more related to habitat characteristics. The results include an implementation of non-destructive ichthyofauna sampling techniques in Brazil, a generation of knowledge about fish ecology and the dissemination of the importance of these protected areas, which will assist management measures and encourage the preservation of the region.

O estabelecimento de reservas marinhas de restrição total (No-take reserves - NTRs), ou seja, áreas com proibição total de pesca, tem sido uma alternativa mundial para preservar a biodiversidade e as funções dos ecossistemas. O Brasil tem importantes NTRs com poucos estudos descrevendo sua relevância e eficiência para a vida marinha. Com isso, o objetivo central desta tese foi avaliar os efeitos de NTRs em assembleias de peixes, testando a hipótese de que as diferenças em riqueza, abundância, biomassa e tamanho corporal dos peixes são mais explicadas pelo status de proteção do que por características ambientais. Para tanto, técnicas inovadoras no Brasil, estéreo-vídeos subaquáticos com isca (Baited Remote Underwater stereo-Videos - stereo-BRUVs) e estéreo-vídeos operados por mergulhador (Diver Operated stereo-Videos - stereo-DOVs) foram testados no Atlântico Sudoeste, comparando com os censos visuais tradicionalmente aplicados (estacionário e transecto), e utilizados para analisar os efeitos da Estação Ecológica Tupinambás e do Parque Nacional Marinho dos Abrolhos nas assembleias de peixes. Para isso, as características das assembleias de peixes em termos de riqueza, biomassa, abundância e tamanho corpóreo, foram comparadas com as áreas onde a pesca é permitida, e a complexidade do habitat foi estimada através das imagens. Em relação à comparação dos métodos, o estéreo-DOV apresentou maior eficiência, amostrando mais riqueza e abundância com menor esforço, e o estéreo-BRUV amostrou uma assembleia específica, composta principalmente por espécies de peixes móveis e de grande porte, geralmente alvos da pesca. Em ambas as NTRs avaliadas, as características das espécies-alvo foram explicadas pelo nível de proteção, enquanto as assembleias de espécies não-alvo foram mais relacionadas às características do habitat. Os resultados incluem a implementação de técnicas não-destrutivas de amostragem da ictiofauna no Brasil, uma geração de conhecimento sobre a ecologia dos peixes e a disseminação da importância dessas áreas protegidas, que auxiliarão nas medidas de manejo e estimularão a sua preservação.
Efeitos de reservas marinhas na assembleia de peixes no Brasil: uma avaliação com o uso de estéreo-vídeos
Keywords: Ecologia marinha; Marine ecology; Amostragem (Estatística); Ictiofauna; Peixes marinhos; Marine fishes; Marine resources conservation; Fishery conservation Law and legislation; Pesca legislação; Unidades de conservação; Ecologia dos recifes de coral